THE URGENCY OF INSTILLING SOFT SKILLS FOR STUDENTS IN THE ERA OF DISRUPTION THROUGH ORGANISATIONAL CULTURE - Khaudli, Muhammad Imam; Nadir, Mirhabun (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Based on the results of the 2020 population census released by the Central Statistics Agency at the end of January, and provides a picture of Indonesia's demographics that has changed a lot from the results of the previous census in 2010. As predicted and analysed by various groups, Indonesia is in a period called the demographic bonus. Interestingly, the 2020 census results show that the composition of the Indonesian population mostly comes from Generation Z or Gen Z (27.94 per cent), which is the generation born between 1997 and 2012. The millennial generation, which is predicted to be the motor of the current community movement, is slightly below Gen Z, which is 25.87 per cent of the total population of Indonesia. This means that the existence of Gen Z plays an important role and influences the development of Indonesia now and in the future. Gen Z, which is filled with teenagers and young adults, many of whom are still studying at universities. From the womb of the university, scholars are born who describe intellectual figures, scientists, and professionals in their respective fields. The most important thing here is actually not the quantity, but the quality of the College itself. A quality university not only produces smart and competitive scholars but must also contribute to improving the welfare of the nation through the knowledge and culture it develops. The problem that arises is that our campuses focus more on providing hard skills and intellectual intelligence. But there are things that are overlooked, namely the importance of teaching soft skills to students considering that these soft skills are also important things to encourage the success of a student and teenager for now and in the future. Based on this background, the author is interested in further research on the Urgency of planting soft skills for students in the era of disruption through organisational culture. This research uses a qualitative descriptive literature method. Based on this research, it is found that students and female students are not only sufficiently filled with knowledge but also need to be equipped with soft skills through acculturation in organisations in an educational institution so that their psychology is formed and becomes a tough and survivable person to face various kinds of situations and conditions faced.